Ghibah dalam Perspektif Hadis - Syifaullah Syifaullah; Nandang Sunandar (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article discusses backbiting in the perspective of hadith. Every human being is required to always do good, be kind, not to hurt people, or to gossip about others. But in reality backbiting seems to have become commonplace in today's society and can cause tension in a society, namely dialogue about other people or negative stories about someone and in religious (Islamic) language it is called backbiting. This study aims to discuss backbiting according to the hadith perspective. This study uses a qualitative approach by applying the thematic method. The formal object of this research is the definition and prohibition of backbiting which are formulated based on hadith themes. The material object of this research is the case. The prohibition of backbiting in the hadith above aims to maintain harmony in social life. The results of this study indicate that hadith themes can be formulated within the theoretical framework of curiosity from a hadith perspective. The discussion of this study explains that curiosity is relevant to aspects of positive mental health and one's well-being which includes digging for information, exploration, asking anyone who can fulfill one's curiosity about something he feels he needs.